CHARACTERIZATION OF THE SOIL OF THE UPPER NILE UNIVERSITY FARM, EL RENK AREA, SOUTH SUDAN - Yong, Stephen Ashouth Atem; Deng , Pio Kur (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
The objectives of this study were to characterize the soil physical and chemical properties and to classify the soil in order to assess the soil water and crop management systems under rain fed and irrigated agriculture in soils of the farm of Faculty of Agriculture as data base for experimental research studies in the farm of the Faculty of Agriculture, Upper Nile University.  . Two soil profiles were excavated in the study area to a depth of 150 cm and fourteen soil samples were collected. The samples were analyzed in the laboratory for their physical and chemical properties. Physical properties results showed that the bulk density of the soil is high (1.7 to 1.9 g ∕ cm3) with low pore space (30% to 37%). The infiltration rate is very low to low (0.8 to 1.2 c ̸ hr.). The saturated hydraulic conductivity is very slow to slow (0.7 to 1, 9 cm ̸ hr.) with high available water (23% to 38%). The chemical results indicate that the soil is neutral to slightly alkaline in reaction (pH 7.3 to pH 8.3) non-saline (ECe 2.6 to 3.4 dSm-1), non-sodic (SAR 1.4 to 8.3), non-calcareous, poor in organic matter (1.7 to 2.4%) and nitrogen content (0.05 to 0.09%). The CEC-values are very high (79 to 87%) and this is due to the high clay content and its Smectitic nature as well. The soil was classified as Typic Haplustertst, very fine, Smectitic, super active, hyper thermic according to Soil Survey Staff (2010). The main limitation in this soil is its deficiency in nitrogen, organic matter and phosphorus well. Therefore, it is necessary to add manures or N- fertilizers for sustainable crop yield. The clay content may cause problems of water management and workability of this soil which require good management.